2012
DOI: 10.1177/193229681200600236
|View full text |Cite
|
Sign up to set email alerts
|

New Criteria for Assessing the Accuracy of Blood Glucose Monitors Meeting, October 28, 2011

Abstract: Glucose meters (GMs) are routinely used for self-monitoring of blood glucose by patients and for point-of-care glucose monitoring by health care providers in outpatient and inpatient settings. Although widely assumed to be accurate, numerous reports of inaccuracies with resulting morbidity and mortality have been noted. Insulin dosing errors based on inaccurate GMs are most critical. On October 28, 2011, the Diabetes Technology Society invited 45 diabetes technology clinicians who were attending the 2011 Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…The degree of BGM accuracy that is desired and required is likely to depend on the clinical needs of individual patients. There is a growing consensus among endocrinologists and other clinicians that the accuracy and precision performance characteristics of each BGM and CGM device should be made available both to the patient and physician, to properly match a BGM device to the appropriate individual or clinical setting (149).…”
Section: Iso Standardsmentioning
confidence: 99%
“…The degree of BGM accuracy that is desired and required is likely to depend on the clinical needs of individual patients. There is a growing consensus among endocrinologists and other clinicians that the accuracy and precision performance characteristics of each BGM and CGM device should be made available both to the patient and physician, to properly match a BGM device to the appropriate individual or clinical setting (149).…”
Section: Iso Standardsmentioning
confidence: 99%
“…[3][4][5][6] Our ranking procedure showed that devices performing highly accurate measurements at low and normal BG levels usually also produce accurate measurements at high BG levels (ranking group A). The number of "benign reading errors" was very low (0.34%).…”
Section: Discussionmentioning
confidence: 99%
“…13 Responses to the consultation process on the new ISO criteria included the suggestion that instead of testing accuracy at BG < 100 mg/dl and > 100 mg/dl, it should be tested at a number of different BG level ranges, making it possible to further differentiate between devices with regard to overall performance. [3][4][5][6] The aim of this more detailed approach to accuracy testing is to identify devices that produce highly accurate measurements, making them suitable for use by patients on intensified insulin therapy. Devices that fail to produce laboratory accuracy at levels below 100 mg/dl might be suitable for use by patients whose therapy regimen excludes the risk of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of uniformity by FDA reviewers creates several inefficiencies, increased costs to the medical device industry, and delays the introduction of new medical products into the market. Having inconsistent regulatory requirements by different FDA reviewers, as was shown by a report from Pricewaterhouse Coopers [50], creates particular challenges for small start-up companies to get investors or venture capitalist funding for new, early-stage technologies [ 51]. The lack of uniform regulatory decision-making also affects the introduction of new technologies, that the FDA had previously identified, as being critical to helping patients [52].…”
Section: Guidancesmentioning
confidence: 99%